Analisis Mistik Hantu Perempuan dalam Novel Ibuku Malang Ibuku Kuyang Karya Nurul Karimah - Urahmah, Nida (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2022)
This study aims to analyze the mystical practices and motivations of female ghosts in the novel Ibuku Malang Ibu Kuyang by Nurul Karimah. This research is a descriptive qualitative research. The data of this research are in the form of words, sentences and dialogues contained in the text of the novel Ibuku Malang Ibuku Kuyang by Nurul Karimah. The steps taken are as follows: (1) Reading the novel Ibuku Malang, Ibuku Kuyang carefully and thoroughly. (2) Collecting data on words, sentences and dialogues in the Novel Ibuku Malang Ibuku Kuyang by Nurul Karimah. (3) After the words, sentences and dialogues in the Novel Ibuku Malang Ibuku Kuyang by Nurul Karimah have been recorded, the next activity is to analyze using the description method. The results of this study show that the mystical practices carried out by female characters become kuyang are teachings that deviate from religion. This mystical practice is carried out by applying kuyang oil around the neck, then the head is separated from the body in search of a sacrifice. While the main character's motivation to become kuyang is to save his household and want to avenge his hurt because his pride has been trampled on by his husband's young wife.